FRUIT PRODUCTION AND QUALITY OF GUAVA AS A FUNCTION OF BIOFERTILIZER AND NITROGEN FERTIGATION IN BRAZILIN SEMIARID - Santana, Elisson Alves; Cavalcante, Ítalo Herbert Lucena; Brito, Diogenes de Souza; Carmo, Raí Nascimento do; Souza, Karla dos Santos Melo de (Emirates Journal of Food and Agriculture, 2017)
Adequate agronomic management is crucial to reach high guava yields that demand a well-defined fertilizer management, including organic fertilizer such as biofertilizers, which have emerged as an important component of the integrated nutrient supply system aiming environmentally better nutrient supply using fertigation systems in Brazil. This way, an experiment was carried out to evaluate the fruit production and quality of guava as a function of biofertilizers and N fertilizing in Brazilian semiarid. The experimental design was in randomized blocks with treatments distributed in a factorial arrangement (5 x 2) referring to biofertilizer concentrations [0, 2.5, 5.0, 7.5 and 10%] and mineral fertilizing with N (fertilization with 50% and 100% of recommended N following soil analysis), with four replications of five plants each. Fruit quality of guava depends on bovine biofertilizer and N fertigation. Biofertilizer promotes significant enhancements on fruit firmness, vitamin C and pH, beyond titratable acidity reduction of guava. fertigation with biofertilizer at 5.66 % increases 13.85 kg plant-1 guava fruit production.